IMPLEMENTATION OF CULTURAL TOURISM DEVELOPMENT PROGRAM BASED ON LOCAL WISDOM IN BEDULU VILLAGE REGENCY OF GIANYAR BALI - Arismayanti, Ni Ketut; Suwena, I Ketut (Universitas Pendidikan Ganesha, 2018)
Implementation of cultural tourism development program in Bedulu village aims to strengthen community empowerment through the development of cultural tourism in accordance with the vision and mission aimed at strengthening village management system; Increasing public participation in tourism activities and development; Improve self-financing and self-help communities and to improve the welfare of the community as well as increasing the original income of Gianyar regency. The implementation approach model includes 1) Participatory Rural Appraisal (PRA) model; 2) Model of Entrepreneurship Capacity Building (ECB), and 3) Transfer Technology Model (TT). Implementation of the program include: 1) Identification of tourism potential at Tourism Attraction Goa Gajah Temple, Relief of Yeh Pulu, Samuan Tiga Temple, and Tegallinggah Cliff Temple; 2) Focus Group Discussion (FGD) with relevant stakeholders on potential and strategic issues of cultural tourism development based on local wisdom in Bedulu Village; 3) Training of Packaging Cultural Tour Packages in Bedulu Village; 4) Technical Training for Tour Guide in Bedulu Village; 5) Making of Guide Book; 6) Making Bedouin Tourism Brochure; 7) Practical English Training in Bedulu Village; 8) Homestay Management Training in Bedulu Village; 9) Culinary Development Training of Bedulu Village; 10) Village Tourism Management in Bedulu Village. The outputs generated in these community service activities include guidebooks; Brochures in English and Japanese; Tutorial on website management; Marketing of tourist attraction located in Bedulu Village through the website, Instagram social media, and video uploaded on YouTube; Capacity building and knowledge as well as community capacity with various training provided.